1977
DOI: 10.2105/ajph.67.7.651
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and growth of infants and young children in a rural Mexican village.

Abstract: Abstract:The relationship between childhood illnesses and growth increments in length and weight was investigated in a 13-month birth cohort of rural Mexican children. Increments in length and weight for each year from birth to three years were related to high and low frequencies of reported time ill during the same period. Seventy-two of the 276 children had already been characterized as exhibiting "growth failure" relative to other members of the cohorts, and this was considered as a separate factor in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“… 17,18 Indeed, these and our subsequent studies suggested that diarrheal illnesses in the first 1–2 years of life may account for a persisting 4 cm shortfall of growth (∼8.2 cm when the effects of intestinal helminths in just the first 2 years of life are included) 19,20 . Similar findings of an important impact of diarrhea on childhood growth have been made in Guatemala, West Africa, Mexico, and Bangladesh 21–26 . When challenged by the argument that catch‐up growth reverses the growth impairment of isolated diarrheal illnesses, 27 analyses of weight gains following a diarrheal illness in our studies in Brazil revealed that recurrent diarrhea reduced weight and, albeit less significantly, height gains by 48% and 21%, respectively, when compared with children who did not have recurrent diarrhea 17,18,28,29 (Table 1).…”
Section: Enteric Infections and Malnutrition: A Vicious Cyclementioning
confidence: 72%
“… 17,18 Indeed, these and our subsequent studies suggested that diarrheal illnesses in the first 1–2 years of life may account for a persisting 4 cm shortfall of growth (∼8.2 cm when the effects of intestinal helminths in just the first 2 years of life are included) 19,20 . Similar findings of an important impact of diarrhea on childhood growth have been made in Guatemala, West Africa, Mexico, and Bangladesh 21–26 . When challenged by the argument that catch‐up growth reverses the growth impairment of isolated diarrheal illnesses, 27 analyses of weight gains following a diarrheal illness in our studies in Brazil revealed that recurrent diarrhea reduced weight and, albeit less significantly, height gains by 48% and 21%, respectively, when compared with children who did not have recurrent diarrhea 17,18,28,29 (Table 1).…”
Section: Enteric Infections and Malnutrition: A Vicious Cyclementioning
confidence: 72%
“…Studies on children have shown an association between the level of bacterial contamination of food and post weaning growth rates (Martorell et al, 1975;Condon-Paoloni et al, 1977;Coates, 1980;Bairagi et al, 1987;Cebu Study Team, 1991;Cebu Study Team, 1992;Walker et al, 1992;Adair et al, 1993). Similar studies in animals have indicated that feeding neonates with diets low in bacteria led to a lower incidence of gastrointestinal disorders and improvement in growth compared with animals that received diets with higher levels of bacterial contamination (Coates, 1980;Speck, 1983;Black et al, 1984b).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies which have asserted that children born earlier in a family's reproductive period are healthier than those born later are based on small crosssectional samples where the individuals have not been systematically re-studied (Condon-Paoloni et at, 1977;Horton, 1988). Furthermore, since most of these studies compared individuals with their own siblings the low birth order individuals were systematically older and members of an earlier cohort than those of higher birth order.…”
Section: Introductionmentioning
confidence: 99%